1998
DOI: 10.1111/j.1469-7793.1998.927bd.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced vasoconstrictor responses in renal and femoral arteries of the golden hamster during hibernation

Abstract: 1. The present study assessed local regulation of vascular tone of euthermic (control), cold control and hibernating golden hamsters. Sympathetic neurotransmission in the renal artery, the long term effects of hibernation on perivascular nerve activity, and the responsiveness of femoral artery to a number of neurotransmitters and hormones with both constrictor and dilator actions during hibernation are described. 2. The contractile responses of the renal arterial rings to transmural nerve stimulation (80 V, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
1

Year Published

1999
1999
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…Increased vasoconstriction described here and by others during fasting‐induced torpor in mice and hibernation in ground squirrels and hamsters (Lyman and O’brien ; Lyman and O’Brien, ; Karoon et al, ; Swoap and Gutilla, ) decreases conductive heat loss in Winter AGS after CHA treatment. CHA induces an immediate drop in O 2 consumption, followed by a delayed decrease in T b in Winter AGS.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Increased vasoconstriction described here and by others during fasting‐induced torpor in mice and hibernation in ground squirrels and hamsters (Lyman and O’brien ; Lyman and O’Brien, ; Karoon et al, ; Swoap and Gutilla, ) decreases conductive heat loss in Winter AGS after CHA treatment. CHA induces an immediate drop in O 2 consumption, followed by a delayed decrease in T b in Winter AGS.…”
Section: Discussionsupporting
confidence: 71%
“…A seasonal decrease in euthermic T b followed by a decrease in thermogenesis precedes the onset of the hibernation season (Sheriff et al, ; Frare et al, ), which coincides with a circannual increase in sleep in euthermic ground squirrels (Walker et al, ) and an increase in vasoconstriction (Karoon et al, ; Swoap and Gutilla, ). Vasoconstriction, sleep, and the decrease in thermogenesis are seasonal strategies employed to achieve energy conservation during hibernation.…”
mentioning
confidence: 99%
“…In a series of studies on hibernation, we showed that changes in expression of transmitters and associated enzymes occurred in both the cardiovascular and visceral systems of hibernating hamsters (77)(78)(79). For example, NOS-positive and endothelin-positive endothelial cells were significantly lower than those observed in active, cold-exposed, or aroused animals, whereas there was an increase in TH-and NPY-immunoreactive perivascular nerves.…”
Section: Long-term (Trophic) Signaling and Plasticitymentioning
confidence: 98%
“…They are often capable of normal activity at low temperatures, relying on increased thermogenesis in visceral organs, adipose tissue and skeletal muscle to regulate core temperature (Jansky, 1973). This elevated aerobic metabolism is likely to require adaptive changes in peripheral oxygen transport, for example vascular adaptations which moderate changes in blood pressure and total peripheral resistance at low temperatures (Brown et al 1993;Karoon et al 1998).…”
mentioning
confidence: 99%